Power Module Lifetime Consumption in Robotic Manufacturing Application - Oskars Bormanis; Janis Zakis; Leonids Ribickis; Frede Blaabjerg (IEEE Access)
This paper investigates the impact of industrial robot operation on the estimated lifetime consumption of hardware components, with a focus on power electronics modules. By converting operational hours to electrical stress and analyzing various robot program types and their corresponding parameters, the study examines how different operational modes can affect the thermal loading and mechanical stress on these power electronics components. These variations can lead to accelerated wear and potential failure. The paper introduces an innovative approach to estimate lifetime consumption based on motor current profiles, enabling real-time analysis of operational data to account for varying robot tasks and stresses. A key contribution of this paper is the translation of motor current data into predictive models for power electronics wear, which allows for more accurate optimization of derating strategies and extends component lifespan. This method enhances predictive maintenance, providing valuable feedback for improving the reliability and efficiency of industrial robots. By assessing the thermal and mechanical impacts on power electronics, the study offers valuable feedback for enhancing the design and operational efficiency of robotic systems in industrial applications. This research contributes to the development of more resilient and durable industrial robots, ensuring better performance and reduced downtime in manufacturing environments.